Сучасний стан популяцій Carlina onopordifolia на Західному Волино-Поділлі - Мельник, В.І.; Скоропляс, І.О.; Баточенко, В.М. (Український ботанічний журнал, 2014)
Рассмотрено современное состояние популяций редкого вида флоры Украины Carlina onopordifolia Bess. ex Szaf., Kulcz. et Pawł (Asteraceae) на западе Волыно-Подолии. Анализ возрастной структуры популяций C. onopordifolia показал качественные различия в зависимости от современного состояния местообитаний. В антропогенно ненарушенных местообитаниях луговых степей преобладают гомеостатические популяции с полночленными спектрами онтогенетических состояний. Создание лесных культур Pinus sylvestris L. на степных склонах приводит к деградации популяций C. onopordifolia на Волыно-Подолии. Предложены рекомендации по улучшению охраны C. onopordifolia на западе Волыно-Подолии. Modern state of population of rare species of Ukrainian flora Carlina onopordifolia Besser ex Szaf., Kulcz. et Pawł (Asteraceae) in Western Wolhynia Podilla are considered. Analysis of the age structure of Carlina onopordifolia populations in Western Wolhynia Podilla has shown qualitative differentiation depending on the modern state of natural habitats. Homeostatic populations with complete ontogenetic state prevail in antropogenically non-disturbed habitats in meadow steppes. Sylvicultures of Pinus sylvestris in steppe slopes cause degradation of Carlina onopordifolia population in Western Wolhynia Podilla. Recommendation for improvement of protection of Carlina onopordifolia in Western Podilla are proposed.